The use of uncertain scenarios in disaster risk reduction: a systematic review. Issue 3 (30th May 2019) - Jafari, Hamid; Jonidi Jafari, Ahmad; Nekoei-Moghadam, Mahmoud; Goharinezhad, Salime
Abstract : Purpose: In recent years, futures study methods, especially scenario analysis, are used to plan for disaster and emergency management. Scenario method is suitable for public level policy making. Scenarios generated alternative descriptive futures in all of the development field such as disaster studies. This paper aims to systematically review the articles that generated scenarios in disaster management to attain gaps, challenges and opportunities related to use of scenario analysis in disasters. Design/methodology/approach: This is a systematic review that was conducted based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The keywords that searched included "disaster, " "emergency, " "crisis, " "disruptive event, " "futures study, " "foresight, " "scenario, " "community-based scenario planning, " "participatory scenario planning, " "scenario planning" and "scenario analysis." The Google Scholar, ISI Web of Science, Science Direct, PubMed and Scopus databases were searched. Findings: A total of 981 article gathered after initial search between electronic databases. At final step, only ten articles included in the study. The selected articles compared according to many aspects. Most of the scenarios that developed in disaster management and planning concentrated on climate change and flooding related hazards. Many of studies developed three or four scenarios that it seems the number is suitable for disaster planning. Originality/value: The paper serves as an original guideline for disaster planning.